Przepisy porządkowe i organizacja warszawskiej parafii ewangelicko-reformowanej w XIX wieku - Michalak, Grzegorz (Saeculum Christianum. Pismo Historyczne, 2019)
The Evangelical Reformed Parish in Warsaw in the 19th century was organised on the basis of the regulations from 1777 and 1839. The Community also showed a large autonomy in relation to the sovereign authorities of the Polish Reformed Church, which was connected with the specifics of Calvinist denomination. The subject of the article is the analysis of the division competences between the main organisational units: the College Church, the Assembly of Members and the pastors.